ACCURACY OF ULTRASOUND IN THE DIAGNOSIS OF UPPER ABDOMINAL PAIN - Imran, Sabina (Journal of Ayub Medical College Abbottabad, 2003)
Background: Upper abdominal pain is one of the commonest complaints in patients seeking medical advice, and in majority of the cases the aetiology is simple and treatable. Ultrasonography is hazard free and cost effective investigation. This study was designed to evaluate the accuracy of ultrasound in the diagnosis of upper abdominal pain. Methods: Ultrasonography using 3.5 MHz convex transducer was performed in patients presenting with upper abdominal pain. Results: Five hundred consecutive cases with upper abdominal pain underwent ultrasonic examination. Positive findings were there in 248 patients while 252 had normal studies. Conclusion: This study showed that ultrasound is an easy and quick investigation in the diagnosis of upper abdominal pain with slightly less than 50% accuracy. Key Words: Ultrasonography, Upper abdominal pain, 3.5 MHz convex transducer.